Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Certainly! To create a table of values for the equation [tex]\(3x + 2y = 6\)[/tex] with [tex]\(x\)[/tex] values ranging from [tex]\(-1\)[/tex] to [tex]\(3\)[/tex], we need to determine the corresponding [tex]\(y\)[/tex] values. Let's solve for [tex]\(y\)[/tex] by isolating it on one side of the equation:
[tex]\[3x + 2y = 6\][/tex]
Subtract [tex]\(3x\)[/tex] from both sides:
[tex]\[2y = 6 - 3x\][/tex]
Now, divide both sides by 2 to solve for [tex]\(y\)[/tex]:
[tex]\[y = \frac{6 - 3x}{2}\][/tex]
We will substitute the given [tex]\(x\)[/tex] values [tex]\([-1, 0, 1, 2, 3]\)[/tex] into this equation to find the corresponding [tex]\(y\)[/tex] values.
1. For [tex]\(x = -1\)[/tex]:
[tex]\[ y = \frac{6 - 3(-1)}{2} = \frac{6 + 3}{2} = \frac{9}{2} = 4.5 \][/tex]
2. For [tex]\(x = 0\)[/tex]:
[tex]\[ y = \frac{6 - 3 \cdot 0}{2} = \frac{6}{2} = 3 \][/tex]
3. For [tex]\(x = 1\)[/tex]:
[tex]\[ y = \frac{6 - 3 \cdot 1}{2} = \frac{6 - 3}{2} = \frac{3}{2} = 1.5 \][/tex]
4. For [tex]\(x = 2\)[/tex]:
[tex]\[ y = \frac{6 - 3 \cdot 2}{2} = \frac{6 - 6}{2} = \frac{0}{2} = 0 \][/tex]
5. For [tex]\(x = 3\)[/tex]:
[tex]\[ y = \frac{6 - 3 \cdot 3}{2} = \frac{6 - 9}{2} = \frac{-3}{2} = -1.5 \][/tex]
Now, we can create the table of values:
[tex]\[ \begin{array}{c|c} x & y \\ \hline -1 & 4.5 \\ 0 & 3 \\ 1 & 1.5 \\ 2 & 0 \\ 3 & -1.5 \\ \end{array} \][/tex]
So the table of values for the graph of [tex]\(3x + 2y = 6\)[/tex] with [tex]\(x\)[/tex] values ranging from [tex]\(-1\)[/tex] to [tex]\(3\)[/tex] is:
[tex]\[ \begin{array}{c|c} x & y \\ \hline -1 & 4.5 \\ 0 & 3 \\ 1 & 1.5 \\ 2 & 0 \\ 3 & -1.5 \\ \end{array} \][/tex]
[tex]\[3x + 2y = 6\][/tex]
Subtract [tex]\(3x\)[/tex] from both sides:
[tex]\[2y = 6 - 3x\][/tex]
Now, divide both sides by 2 to solve for [tex]\(y\)[/tex]:
[tex]\[y = \frac{6 - 3x}{2}\][/tex]
We will substitute the given [tex]\(x\)[/tex] values [tex]\([-1, 0, 1, 2, 3]\)[/tex] into this equation to find the corresponding [tex]\(y\)[/tex] values.
1. For [tex]\(x = -1\)[/tex]:
[tex]\[ y = \frac{6 - 3(-1)}{2} = \frac{6 + 3}{2} = \frac{9}{2} = 4.5 \][/tex]
2. For [tex]\(x = 0\)[/tex]:
[tex]\[ y = \frac{6 - 3 \cdot 0}{2} = \frac{6}{2} = 3 \][/tex]
3. For [tex]\(x = 1\)[/tex]:
[tex]\[ y = \frac{6 - 3 \cdot 1}{2} = \frac{6 - 3}{2} = \frac{3}{2} = 1.5 \][/tex]
4. For [tex]\(x = 2\)[/tex]:
[tex]\[ y = \frac{6 - 3 \cdot 2}{2} = \frac{6 - 6}{2} = \frac{0}{2} = 0 \][/tex]
5. For [tex]\(x = 3\)[/tex]:
[tex]\[ y = \frac{6 - 3 \cdot 3}{2} = \frac{6 - 9}{2} = \frac{-3}{2} = -1.5 \][/tex]
Now, we can create the table of values:
[tex]\[ \begin{array}{c|c} x & y \\ \hline -1 & 4.5 \\ 0 & 3 \\ 1 & 1.5 \\ 2 & 0 \\ 3 & -1.5 \\ \end{array} \][/tex]
So the table of values for the graph of [tex]\(3x + 2y = 6\)[/tex] with [tex]\(x\)[/tex] values ranging from [tex]\(-1\)[/tex] to [tex]\(3\)[/tex] is:
[tex]\[ \begin{array}{c|c} x & y \\ \hline -1 & 4.5 \\ 0 & 3 \\ 1 & 1.5 \\ 2 & 0 \\ 3 & -1.5 \\ \end{array} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.